Is Slumdog Millionaire a Retelling of the Ramayana? - Blizek, William L. (The journal of religion and film, 2015)
Is a banner with a picture of Rama and Sita on it and the word, “Ramayana,” the only link between the film Slumdog Millionaire and the great Hindu epic? In this paper we explore elements in the film that correspond to elements in theRamayana. There is no one-to-one correlation, and some relationships between the two are, in fact, mirror images. However, there are enough correlations and influences to suggest that the film might be considered a retelling of theRamayana. We also acknowledge though that there are also features of the film that some would find offensive and that would lead them to reject this idea that Slumdog Millionaire is a retelling of the epic.